Introduction to cyberspace security discipline - Huanguo ZHANG; Ruiying DU (网络与信息安全学报)
With rapidly development of electronic information technology and industry,human society comes into information age.In the information age human lives and works in cyberspace.There for,it is the base requirement for human to ensure cyberspace security in the information age.Now,our country has established whole one-level discipline of cyberspace security.So the top priority for us is that should discuss overall the architecture and base theory of cyberspace security discipline.It include the contents as follows:the concept of cyberspace and cyberspace security,the definition of cyberspace security discipline,main research area and contents of cyberspace security discipline,base theory and method theory of cyberspace security discipline.Consequently,we should correctly understand and know well the architecture and base theory of cyberspace security discipline.It is very important not only for discipline construction end personnel training but also for science research and industry development in our country.